Effect of Bovatec and Ralgro implants on finishing steer performance - Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station, 2011)
Cattle fed Bovatec consumed 17.4% less feed and were 17.7% more efficient than controls, with no effect on gain. Ralgro implants improved gain 12% and feed efficiency 6.9%, with no effect on feed intake. Bovatec and Ralgro combined had an additive effect on feed efficiency.
Keywords: Beef; Implants; Bovatec; Ralgro; Steer performance